Study of mixing in Miniaturized Intensified Reactor (MIR) - Gopinathan, Subramaniam (Universiti Sains Malaysia, 2017)
Mixing in industrial is a common process which helps the process of heat transfer, chemical reaction and mass transfer process. Mixing process is a very important process to make sure the quality of the final product will be derived by that quality of the mix. Application of mixing process intensification in chemical engineering area is growing and widely used where the use of microfluidic devices has already been upgraded to production scale. An essential method of process intensification which are microreactor technology, offers potential benefits to the future of chemical engineering due to the well-defined high specific interfacial area available for heat and mass transfer, which increases transfer rates, and enhances safety resulting from low hold-ups. In relation to the time-scale of chemical kinetics, diffusive transport in micro-devices is faster than in conventional mixers. To exploit the resulting potential, the mixing behavior of flow mixers on micro-scales needs to be further investigated. In this work, experiment conducted for different inlet flowrate and absorbance measurement towards the mixing quality The results provide some support of transport phenomena on mixing that occurred in the microchannel. The results demonstrated that inlet geometry has significance effects on the mixing performance. Y-shape uses low inlet velocity and 0 mm mixing length resulted in faster mixing process. Y-shaped microchannel shows better mixing quality than T-shaped microchannel.